1997
DOI: 10.2337/diab.46.5.758
|View full text |Cite
|
Sign up to set email alerts
|

Hsp60 Peptide Therapy of NOD Mouse Diabetes Induces a Th2 Cytokine Burst and Downregulates Autoimmunity to Various β-Cell Antigens

Abstract: A peptide of the human 60-kDa heat-shock protein (hsp60), designated p277, was found to be useful as a therapeutic agent to arrest the autoimmune process responsible for diabetes in nonobese diabetic (NOD) mice. The effectiveness of peptide treatment was associated with the induction of peptide-specific antibodies of the IgG1 but not of the IgG2a isotype, suggesting the possibility that a Th2-type response may have been induced. We now report that the effectiveness of p277 treatment is associated with the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
73
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 0 publications
4
73
1
Order By: Relevance
“…For the same two stimuli no difference was seen in IL-10 or IL-4 responses between ICA positive and their respective diabetic cotwins. A Th2 bias of the response to hsp60 in discordant twins of low diabetes risk is consistent with recent studies in NOD mice, where a Th1 bias of the T cell response to hsp60 was found to correlate with disease progression in mice whereas a Th2 bias was found in animals protected from diabetes development [6]. In man, previous studies of a possible association between hsp60 autoimmunity and Type I diabetes did not yield firm conclusions [3,7,8].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For the same two stimuli no difference was seen in IL-10 or IL-4 responses between ICA positive and their respective diabetic cotwins. A Th2 bias of the response to hsp60 in discordant twins of low diabetes risk is consistent with recent studies in NOD mice, where a Th1 bias of the T cell response to hsp60 was found to correlate with disease progression in mice whereas a Th2 bias was found in animals protected from diabetes development [6]. In man, previous studies of a possible association between hsp60 autoimmunity and Type I diabetes did not yield firm conclusions [3,7,8].…”
Section: Discussionsupporting
confidence: 75%
“…It is therefore conceivable that the immune response to hsp60 is of relevance to the disease process in islets. Recent studies suggest that hsp60 is a unique autoantigen because it not only is recognised by T cells through classic rules of MHC dependent peptide presentation [6] but is also a ªdangerº antigen to the innate immune system. This means, macrophages, endothelial cells and other primitive immune cells are able to recognise exogenous hsp60 and secrete mediators with potent modulatory effects on subsequent T cell responses [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, analogous to the 1-9Nac MBP-induced resistance in EAE mice, immunizing NOD mice with p277 peptide clinically arrested the autoimmune diabetic process. Interestingly, the effectiveness of this peptide treatment was associated with the transient activation of anti-p277 splenic TH2 cells (39). A similar observation was also made by Chaturvedi et al (40), when immunizing NOD mice with a different self-peptide I-A␤ g7 54-76.…”
Section: Discussionsupporting
confidence: 62%
“…These include islet-specific Ags, like insulin, and other nonislet-specific Ags, like glutamic acid decarboxylase (GAD) 3 65, carboxypeptidase H, and IA-2 among others (11,12). Of all the known autoantigens implicated in the disease process, treatment with only insulin, GAD 65, and the heat shock protein (hsp) 60 peptide p277 can protect nonobese diabetic (NOD) mice from disease (13)(14)(15)(16). Insulin and GAD 65 are also the most prominent islet autoantigens shown to be recognized by peripheral T cells from type 1 diabetes patients (17,18).…”
mentioning
confidence: 99%